The blood sugar solution cookbook : more than 175 ultra-tasty recipes for total health and weight loss - Hyman, Mark, 1959- (Little, Brown and Company, 2013)
Features 200 recipes that exchange toxic mass-produced foods with made-at-home versions including Chicken Satay with Peanut Sauce, Mexican Shrimp Ceviche, and Raspberry Banana Cream Pie Smoothies that will maintain balanced insulin and blood sugar levels and promote a healthier lifestyle.